(untitled) (One Health & Risk Management, 2023)
Introduction. Doctors and pharmacists are considered key-players in the fight against doping in sports, so they should be perfectly positioned to educate, advise and guide both elite and recreational athletes on doping issues. At the same time, the published data revealed that medical specialists do not possess sufficient anti-doping knowledge and practical skills, so the development and the application in practice of the university and post-graduate anti-doping training programs will greatly contribute to the eradication of doping in sports. The aim of this research was to assess the anti-doping knowledge among medical students in order to develop the recommendations for its improvement. Material and methods. In September and October 2022 a cross-sectional study was performed by using an anonymous self-administered questionnaire consisting of 26 questions. Medicine 2 Faculty students from their IV-VI-th year of study were invited via social media to complete the questionnaires. The statistical analysis was performed using SPSS 23.0 software. Results. The survey involved 60 participants: females – 41,1% and males – 58.9% with the mean age 26.5 years (26.6 years in females and 25.8 years in males). Almost all of the study participants were students from Israel, with the majority being in the 4th and 5th year of studies. 50% of respondents mentioned that doping is a serious problem for performance sports, while other 50% of students did not consider it a problem and were unaware of it. About 53.6% of study participants know about the WADA and NADA, but 46.4% had not heard about these organizations. Only 25% of the students gave a clear answer regarding the antidoping rule violation mentioning the presence of a prohibited substance in an athlete’s sample; use by an athlete of a prohibited substance; evading, refusing or failing to submit to sample collection; possession of a prohibited substance or prohibited association; acts to discourage reporting to authorities; etc. 69.6% of study participants studied about prohibited substances at University, while others didn’t know anything about them. Therapeutic use exemption (TUE), an important doping prevention measure, authorizes athletes to use prohibited substances for therapeutic purposes to restore health while attending a sport event. The data obtained from the study revealed that only 48.2% of respondents know about TUE, and 21.4% have heard something about it. In case the athlete accepted or procured a prohibited substance, 37.5% of participants stated that they would report it to the national anti-doping organizations; 33.9% stated they would discuss about the inadmissibility to use it with the athlete; 23.2% would seek additional information, and 5.4% would not take any measure. Conclusions. Doping remains a current public health problem because the lack of anti-doping education in medical students. The development and implementation of undergraduate and postgraduate anti-doping programs will significantly improve anti-doping knowledge and practical skills among medical students. Notă: The study was carried out with the financial support of the project "The phenomenon of juvenile doping in athletes in the bioethical and medical approach", number: 20.80009.8007.19, financed by NARD..